Fe-based alloys and their shielding properties against directly and indirectly ionizing radiation by using FLUKA simulations. (4th February 2021) - Al-Buriahi, M S; Gaikwad, D K; Hegazy, H H; Sriwunkum, Chahkrit; Neffati, R
Abstract: Effective shielding material is an essential demand to minimize the harmful effects of ionizing radiation in various nuclear and medicine facilities. In this article, we report on the directly and indirectly ionizing radiation shielding properties of Fe-based alloys in the chemical composition of Fe83 /B13−x /Cx /Si3 /P1, where x is ranging from 0 up to 4 mol%. Indirectly ionizing radiation studies include the interactions of the Fe-based alloys with the neutral radiation such as photon (X and gamma rays) and neutron. The photon interaction parameters (e.g. LAC, MAC, MFP, EAC, HVL, SGRC, and dose rate) were obtained by using FLUKA simulations and theoretical calculations for energies 0.6, 1.25, 1.5, 2, 3, 5, 10, and 15 MeV. The neutron interaction parameters were investigated for thermal and fast neutrons in terms of scattering, absorption, and removal cross sections. Moreover, directly ionizing radiation studies include the interactions of the selected alloys with charged particles such as electron, proton, alpha, and carbon. The obtained results indicate that a maximum dose rate (∼10 8 R hr −1 ) is observed in the 1 mm thickness of FBCSP-A, FBCSP-B, FBCSP-C, FBCSP-D and FBCSP-E alloys at 15 MeV. While, the minimum dose rate is noted at the lower E side (0.6 MeV) in the 5 mm thickness of Fe-based alloys, and decreased from 74.589 × 10 5 to 74.644 × 10 5 (R hr −1 ) for FBCSP-A to FBCSP-E alloys. It can be concluded that the Fe-based alloys are useful for shielding applications against directly and indirectly ionizing radiation as compared with traditional, common, and commercial shields.